4-Hydroxy-3-methoxybenzaldehyde-nicotinamide(1/1) - How, F.N.F.; Ali, Hapipah Mohd; Khaledi, H.; Amalina, M.S. (International Union of Crystallography, 2011)
In the title compound, C(6)H(6)N(2)O center dot C(8)H(8)O(3), an equimolar co-crystal of nicotinamide and vanillin, the aromatic ring and the amide fragment of the nicotinamide molecule make a dihedral angle of 32.6 (2)degrees. The vanillin molecule is almost planar, with an r.m.s. deviation for all non-H atoms of 0.0094 angstrom. The vaniline and nicotinamide aromatic rings are nearly coplanar, the dihedral angle between them being 3.20 (9)degrees. In the crystal, the two components are linked through N-H center dot center dot center dot O and O-H center dot center dot center dot N hydrogen bonds into chains along the a axis. The chains are connected via C-H center dot center dot center dot O interactions, forming a three-dimensional polymeric structure.